MANAJEMEN BIMBINGAN DAN KONSELING KARIER SISWA SMK 1 ANGKASA MARGAHAYU KABUPATEN BANDUNG - Defauzi, Prisna; Yoseptry, Ricky; Ahadiat, Ahadiat; Kusmiyati, Nany (STKIP PGRI Situbondo, 2024)
The aim of this research is to examine the management of career guidance and counseling for students at SMK 1 Angkasa Margahayu, Bandung Regency, with the research focus referring to George R. Terry's management theory, namely planning, organizing, implementing and supervising. This research uses a qualitative approach with qualitative descriptive methods. Meanwhile, this type of research is field research. Research data was collected using observation, interviews and documentation methods. Data collected from this technique was analyzed using data reduction, data presentation and data verification, data validity was obtained using data triangulation. The results of this research show that student career guidance and counseling at SMK 1 Angkasa Margahyu uses the principles of the management system. The indicators are related to continuous improvement including improving quality and competency.